The Properties and Origin of Kuiper Belt Object Arrokoth's Large Mounds - S. A. Stern; O. L. White; W. M. Grundy; B. A. Keeney; J. D. Hofgartner; D. Nesvorný; W. B. McKinnon; D. C. Richardson; J. C. Marohnic; A. J. Verbiscer; S. D. Benecchi; P. M. Schenk; et al. (The Planetary Science Journal, 2023)
We report on a study of the mounds that dominate the appearance of Kuiper Belt Object (486958) Arrokoth's larger lobe, named Wenu. We compare the geological context of these mounds and measure and intercompare their shapes, sizes/orientations, reflectance, and colors. We find the mounds are broadly self-similar in many respects and interpret them as the original building blocks of Arrokoth. It remains unclear why these building blocks are so similar in size—and this represents a new constraint and challenge for solar system formation models. We then discuss the implications of this interpretation.